а) домножим обе части на x+3. Тогда
4 = -2x(x+3)
4 = -2x^2 - 6x
2x^2 + 6x + 4 = 0
D = 36 - 32 = 4
x1 = (-6 + 2)/4 = -1
x2 = (-6-2)/4 = -2
Б) Домножим обе части на (x+3)(x-1). Получаем
3(x-1) + 5x(x+3) = (x+3)(x-1)
3x-3+5x^2+15x = x^2 + 3x - x - 3
3x-3x+x+5x^2-x^2-3+3+15x = 0
4x^2 + 16x = 0
4(x^2 + 4x) = 0
x^2 + 4x = 0
D = 16
x1 = (-4-4)/2 = -4
x2 = (-4+4)/2=0
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
а) домножим обе части на x+3. Тогда
4 = -2x(x+3)
4 = -2x^2 - 6x
2x^2 + 6x + 4 = 0
D = 36 - 32 = 4
x1 = (-6 + 2)/4 = -1
x2 = (-6-2)/4 = -2
Б) Домножим обе части на (x+3)(x-1). Получаем
3(x-1) + 5x(x+3) = (x+3)(x-1)
3x-3+5x^2+15x = x^2 + 3x - x - 3
3x-3x+x+5x^2-x^2-3+3+15x = 0
4x^2 + 16x = 0
4(x^2 + 4x) = 0
x^2 + 4x = 0
D = 16
x1 = (-4-4)/2 = -4
x2 = (-4+4)/2=0